2001
DOI: 10.2337/diacare.24.7.1175
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity and Serum Insulin Concentrations in Two Populations at High Risk for Type 2 Diabetes but Differing by BMI

Abstract: OBJECTIVE -Physical activity and insulin sensitivity are related in epidemiological studies, but the consistency of this finding among populations that greatly differ in body size is uncertain. The present multiethnic epidemiological study examined whether physical activity was related to insulin concentrations in two populations at high risk for diabetes that greatly differ by location, ethnic group, and BMI.RESEARCH DESIGN AND METHODS -The study populations consisted of 2,321 nondiabetic Pima Indian men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 32 publications
5
36
1
1
Order By: Relevance
“…Fasting hyperglycemia predominantly reflects hepatic insulin resistance with normal muscle insulin sensitivity; postload hyperglycemia is characterized by moderate-to-severe skeletal muscle insulin resistance with normal or mildly reduced hepatic insulin sensitivity (34). This might explain the association with 2-h PG but not FPG in our study, since physical activity is directly associated with improved insulin sensitivity (35,36). Furthermore, the absence of an association with FPG concurs with the findings from controlled clinical studies in people with and without type 2 diabetes who have generally observed no changes in FPG following exercise training (37)(38)(39).…”
Section: Discussionsupporting
confidence: 59%
“…Fasting hyperglycemia predominantly reflects hepatic insulin resistance with normal muscle insulin sensitivity; postload hyperglycemia is characterized by moderate-to-severe skeletal muscle insulin resistance with normal or mildly reduced hepatic insulin sensitivity (34). This might explain the association with 2-h PG but not FPG in our study, since physical activity is directly associated with improved insulin sensitivity (35,36). Furthermore, the absence of an association with FPG concurs with the findings from controlled clinical studies in people with and without type 2 diabetes who have generally observed no changes in FPG following exercise training (37)(38)(39).…”
Section: Discussionsupporting
confidence: 59%
“…In our study, physical activity was a significant determinant of the ISI only when not adjusted for either weight or percent body fat. This is in contrast to other studies that have reported associations between physical activity or fitness levels and measures of insulin sensitivity independent of various measures of body mass or body composition in adults (11,14,29) and children (12,13,28). None of the studies in children, however, used DLW to measure physical activity level but instead used VO 2max (12,28) and/or questionnaire variables (12,13).…”
Section: Changes In Insulin Sensitivity During Childhood In Pima Indianscontrasting
confidence: 49%
“…Dengel et al (11) reported that 10 months of aerobic training and weight loss had additive effects on improving glucose homeostasis in obese sedentary men, suggesting that physical activity and adiposity have independent mechanisms for altering insulin sensitivity. Crosssectional associations between insulin sensitivity and physical activity levels independent of adiposity have been reported in children and adolescents (12,13), and an association of physical activity with insulin levels independent of BMI was recently reported in Pima Indian adults (14). Considering the difficulty of treating childhood obesity, as well as the increase in adiposity that was observed in Pima Indian children between 5 and 10 years of age (6), it is important to determine whether changes in physical activity during this time had an independent impact on changes in insulin sensitivity.…”
mentioning
confidence: 99%
“…The validity of this questionnaire has been measured among participants at risk for T2D (27) . In addition, the MAQ assesses both current and over-the-past-year leisure and occupational activities.…”
Section: Anthropometric Measurementmentioning
confidence: 99%